Mining through the National Security Lens - Cruz, Jerome Patrick D (Archīum Ateneo, 2017)
Mining is a volatile industry in the Philippines notwithstanding its potential importance to the country’s industrialization and development. Due in part to longstanding debates on its environmental impact and contributions to tax revenues, as well as issues with existing mining laws, mining has become a divisive issue and has failed to contribute more significantly to the country’s economy. This study examines the Philippine mining industry in the context of promoting national security through industrialization. It examines how mining could be part of a robust value chain — going beyond the present view that it is simply a source of tax revenues. Using this national security and industrial policy lens emphasizes the potentially important role of mining in sustaining the Philippines’ sustained economic development. This is even more critical when one considers that China — a country which has a simmering territorial dispute with the Philippines — already supplies the lion’s share of the country’s steel. And this is trend that could be reinforced further by China’s effort to promote its Belt and Road Initiative and the Philippines’ effort to ramp up its infrastructure investments through the Duterte administration’s Build-Build-Build program.